2023
DOI: 10.1186/s12883-023-03087-9
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid extension and unfavorable outcomes in patients with supratentorial intracerebral hemorrhage

Abstract: Objective Our study aimed to investigate the association between the subarachnoid extension of intracranial hemorrhage (SAHE) and clinical outcomes in patients with supratentorial intracerebral hemorrhage (ICH). Methods We analyzed the data from a prospective, multi-center, and registry-based database. Two experienced investigators independently assessed ICH imaging data. We compared baseline characteristics and follow-up outcomes. Multivariable lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Surgical instrumentation of the lumbosacral spine led most frequently to post-operative RCH [9]. However, as reported by Wang et al, even less invasive procedures, such as repeated lumbar punctures, are likely to cause RCH [10]. As highlighted by Sturiale et al, intentional or accidental intra-operative dural tearing was overall reported in about 93% of patients who developed post-operative RCH [9].…”
Section: Discussionmentioning
confidence: 94%
“…Surgical instrumentation of the lumbosacral spine led most frequently to post-operative RCH [9]. However, as reported by Wang et al, even less invasive procedures, such as repeated lumbar punctures, are likely to cause RCH [10]. As highlighted by Sturiale et al, intentional or accidental intra-operative dural tearing was overall reported in about 93% of patients who developed post-operative RCH [9].…”
Section: Discussionmentioning
confidence: 94%